Mediastinal FDG-positive lymph nodes simulating melanoma progression: drug-induced sarcoidosis like/lymphadenopathy related to ipilimumab. Issue 1 (28th January 2021) - González-Cruz, Carlos; Bodet, Domingo; Muñoz-Couselo, Eva; García-Patos, Vicente
Abstract : Drug-induced sarcoidosis-like reactions (DISRs) are systemic granulomatous diseases that develop in the context of a new drug onset. Ipilimumab is an immune checkpoint inhibitor (ICI) approved for the treatment of advanced melanoma which has been associated with DISR. Differential diagnosis between tumour progression and DISR by positron emission tomography/computed tomography (PET/CT) in patients treated with an ICI can be a challenge. A 31-year-old woman was diagnosed with a stage IIIB melanoma in her back. Ipilimumab 10 mg/kg was initiated. After 1 month of finishing the treatment a routine, PET/CT showed multiple enlarged mediastinal and hilar lymph nodes FDG-positive. A transbronchial biopsy showed sarcoid-like granulomatous infiltration which favoured the diagnosis of DISR related to ipilimumab. The patient remained asymptomatic and lymphadenopathy regressed progressively after 11 months. Our work highlights the importance of differentiating DISR from tumour progression, before unnecessary changes in therapeutic strategies. PET/CT is a useful diagnostic tool for its follow-up.